2018
DOI: 10.3382/ps/pey097
|View full text |Cite
|
Sign up to set email alerts
|

Effect of guanidinoacetic acid supplementation on live performance, meat quality, pectoral myopathies and blood parameters of male broilers fed corn-based diets with or without poultry by-products

Abstract: Creatine is a nitrogenous compound naturally occurring in animal tissues and is obtained from dietary animal protein or de novo synthesis from guanidinoacetic acid (GAA). The dietary supply of this semi-essential nutrient could be adversely compromised when feeding purely vegetable-based diets. The objective of this experiment was to evaluate the effects of GAA supplementation in broilers fed corn-based diets with or without the inclusion of poultry by-products (PBP) on live performance, carcass and cut up yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 42 publications
2
35
1
Order By: Relevance
“…a-c Means within a row with different superscripts are significantly different (p < 0.05). Sapcota et al (2018) confirmed that GAA at a level of 600 mg/ kg can effectively improve feed conversion and body weight gain in diets containing animal meals. In addition, the growth performance was not further increased when diet was supplemented with more than 600 mg/kg GAA, which suggested that the effect of GAA was not positively correlated with the incremental dosages.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…a-c Means within a row with different superscripts are significantly different (p < 0.05). Sapcota et al (2018) confirmed that GAA at a level of 600 mg/ kg can effectively improve feed conversion and body weight gain in diets containing animal meals. In addition, the growth performance was not further increased when diet was supplemented with more than 600 mg/kg GAA, which suggested that the effect of GAA was not positively correlated with the incremental dosages.…”
Section: Discussionmentioning
confidence: 57%
“…Although in the present study birds fed diets with 2% fish meal during 1–21 days of age, the effective dosage was in consistent with that reported by Michiels et al () and Degroot (). The study of Córdova‐Noboa, Oviedo‐Rondón, Sarsour, Barnes, Sapcota et al () confirmed that GAA at a level of 600 mg/kg can effectively improve feed conversion and body weight gain in diets containing animal meals. In addition, the growth performance was not further increased when diet was supplemented with more than 600 mg/kg GAA, which suggested that the effect of GAA was not positively correlated with the incremental dosages.…”
Section: Discussionmentioning
confidence: 92%
“…In broilers fed diets with variable energy content and supplemented with GAA, Tabatabaei Yazdi et al (2017) observed increased concentrations of phosphocreatine, ATP/ADP, and phosphocreatine/ATP ratios in breast muscle. Likewise, Córdova-Noboa et al (2018b) found that the dietary GAA supplementation (600 g/ton) increased the serum concentrations of creatine and GAA in broiler chickens by 1.6 and 9.2 times, respectively, compared to non-supplemented broilers ( Figure 2 ). In the same way, Nasiroleslami et al (2018) had reported higher CK activity in GAA-supplemented broilers than in the control group.…”
Section: Gaa Used As Feed Additive For Poultrymentioning
confidence: 83%
“…Generally, the reduction in the severity of myopathies has been associated with growth rate reduction ( Petracci et al, 2015 , 2019 ; Aviagen, 2019 ). Recent studies have reported that the dietary inclusion of guanidino acetic acid (GAA) partially ameliorated the occurrence and severity of WB myopathy while maintaining or improving live performance and breast meat yield ( Córdova-Noboa et al, 2018a , b ; Aviagen, 2019 ; Vargas, 2019 ). GAA is a metabolite precursor of creatine, a central energy molecule in muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Analogously, different coccidiosis control approaches (Dalle Zotte, Tasoniero, Russo, Longoni, & Cecchinato, ) and dietary supplementation with antioxidants (vitamin E, C, and selenium) and organic trace minerals (Kuttappan et al., ; Sihvo et al., ; Sirri et al., ), which overall have been supposed to reduce muscle fiber oxidative stress associated with breast abnormality progress, did not result in any true mitigation effects. On the other hand, a slight reduction of moderate cases of WB has been obtained by dietary supplementation of guanidinoacetic acid used a precursor of creatine, but strong interaction with diet composition was found (Cordoba‐Noboa et al., ,b). Recently, it was demonstrated that an increase of arginine:lysine ratio can have a mitigation effect on breast meat abnormalities (Zampiga, Soglia, Petracci, Meluzzi, & Sirri, ) though a similar study led to a divergent outcome (Bodle et al., ).…”
Section: Means Of Alleviation: Facts and Challengesmentioning
confidence: 99%